Optimalisasi Penerapan K3 melalui Edukasi Partisipatif pada Pekerja Pabrik Percetakan dan Penjilidan di Gedangan Sidoarjo (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
This community service activity is motivated by the low level of workers’ awareness and understanding of Occupational Safety and Health (OSH) implementation in the printing and binding industry in Gedangan, Sidoarjo. The purpose of this program is to optimize OSH implementation through participatory education to improve workers’ knowledge and safe work behavior. The method used is a participatory approach involving problem identification, focus group discussions (FGD), interactive education, technical training, as well as mentoring and evaluation through pre-test and post-test. The results show a significant increase in workers’ understanding, with average scores rising from 56.25% to 83.75% (an increase of 27.5%). In addition, behavioral changes were observed, including improved compliance in using personal protective equipment (PPE) and the ability to identify workplace hazards. The program also resulted in the formation of OSH cadres as local change agents. Therefore, participatory education has proven effective in improving OSH implementation and fostering a sustainable safety culture.